SURVEY OF NATURAL DYE YIELDING PLANTS IN VELLAMCODE PANCHAYATH, KANYAKUMARI DISTRICT, TAMILNADU, SOUTH INDIA - Anusha, S; Mary Kensa, V; Lakshmanan R (The Bioscan, 2024)
India is known across the world for its rich biodiversity and its flora and fauna. Natural dyes are the way ahead for the textile industry and with the anticipated increase in demand in the upcoming decade it becomes essential that an extensive research is done to ensure that there are plans and guidelines in place to protect our biodiversity while maintaining the increase in demand. Natural dyes are derived from natural elements like plants, animals, minerals and microbial sources. Plants are considered to be the major source of natural dyes. In this current investigation, the number of dye yielding plants and the availability of natural dyes are recorded.